2005
DOI: 10.1177/154596830501900207
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ischemic Lesion Volume and Functional Status in the 2nd Week after Middle Cerebral Artery Stroke

Abstract: Lesion volume is moderately to strongly related to the functional status in the 2nd week poststroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 31 publications
0
33
1
Order By: Relevance
“…Another potential limitation is the clinical utility of a measure that predicts infarct volume. A few authors have reported associations with DWI volume and functional scales (such as the Barthel Index) [16,17] but it will be important to determine that a clinical assessment of volume of ischemia truly corresponds to tangible patient outcomes. The NIHSS is least associat-ed with functional outcomes in patients with cortical strokes [4]; it is likely that the NIHSS-plus would be more predictive than the NIHSS particularly for cortical strokes, as illustrated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation is the clinical utility of a measure that predicts infarct volume. A few authors have reported associations with DWI volume and functional scales (such as the Barthel Index) [16,17] but it will be important to determine that a clinical assessment of volume of ischemia truly corresponds to tangible patient outcomes. The NIHSS is least associat-ed with functional outcomes in patients with cortical strokes [4]; it is likely that the NIHSS-plus would be more predictive than the NIHSS particularly for cortical strokes, as illustrated in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with middle cerebral artery strokes, ischemic lesion volume correlates strongly with NIHSS score. 7 On the other hand, outcome-preference surveys indicate that a majority of stroke victims or potential stroke victims most value a complete functional recovery. 8,9 The latter is best reflected by an mRS score of 0 or 1.…”
Section: Methodsmentioning
confidence: 99%
“…The scale contains domains similar to the NIHSS: level of consciousness, best gaze, visual field, facial palsy, and motor arm and motor leg, for which each domain is categorically rated by level of impairment to absence of abnormality (see Wilde et al, 2010 for a more detailed description of the modifications to the NIHSS). Although the NIHSS has undergone adequate validation in stroke populations through comparison with other stroke scales (D'Olhaberriague et al, 1996;Lyden and Lau, 1991;Lyden et al, 2001;Young et al, 2005), the Glasgow Outcome Scale, and imaging (Brott et al, 1989;Derex et al, 2004;Lyden et al, 2004;Meyer, 1998;Saver et al, 1999;Schiemanck et al, 2005), measures of neurological functioning such as the NIHSS are rarely validated against what is arguably the gold standard for neurological functioning: a clinical neurological examination performed by a neurologist. Accordingly, we evaluated the construct validity of the NOS-TBI using a quantified clinical neurological examination in a sample of patients with TBI currently undergoing post-acute rehabilitation.…”
Section: Introductionmentioning
confidence: 99%